Studies on the adsorption and kinetics of photodegradation of a model compound for heterogeneous photocatalysis onto TiO2 - Valente, Jose Pedro S.; Padilha, Pedro M.; Florentino, Ariovaldo O. (Elsevier B.V., 2006)
An investigation was made on the adsorption and kinetics of photodegradation of potassium hydrogenphthalate in an aqueous suspension of TiO2. Two models, Langmuir and Freundlich, were used to describe the adsorption process and the model proposed by Langmuir-Hinshelwood (L-H) was employed to describe the kinetics of the photodecomposition reactions of hydrogenphthalate. The results of the adsorptions were fitted to the models proposed by Langmuir and Freundlich. Adsorption was found to be a function of the temperature, with adsorption capacity increasing from 2.4 to 4.5 mg/g when the temperature rose from 20 to 30 degrees C. The kinetic model indicates that the rate constant, k, of the first order reaction, is high in the 10.0 to 100 mg/l interval, which is coherent with the low value of the adsorption constant, K. The results fitted to the L-H model led to an equation that, within the range of concentrations studied here, theoretically allows one to evaluate the photodegradation rate. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: potassium hydrogenphthalate; TiO2; adsorption-kinetics; Langmuir; Freundlich; Langmuir-Hinshelwood